Identification of tumor associated neutrophils-related genes in triple-negative breast cancer for predicting prognosis and therapeutic response through integrated single-cell analysis - Li, Koukou; Gong, Lingli; Zhang, Yuxuan; Yang, Lihua; Xu, Daxing; Wang, Mei; Hu, Yaling (Frontiers in Immunology, 2025)
Tumor-associated neutrophils (TANs) significantly influence tumor development, immune system suppression, and the spread of cancer in triple-negative breast cancer (TNBC). However, their molecular pathways and potential for therapy are not completely understood. We utilized Seurat and Harmony to perform quality control, batch correction, and cell annotation on single-cell RNA-seq data from TNBC patients (GSE222854). Comprehensive bioinformatics approaches—including immune infiltration analysis, GSEA, GSVA, drug sensitivity profiling, and ligand-receptor interaction network analysis were combined with functional validation (colony formation and Transwell assays) and clinical correlation studies via polychromatic immunofluorescence. Four TAN-associated genes (RASGRP4, TIMM10B, TNFRSF13C, and GRAP) with distinct roles in TNBC progression were identified. Functional assays revealed pro-tumorigenic effects of RASGRP4, TIMM10B, and GRAP, whereas TNFRSF13C exhibited tumor-suppressive properties. Clinically, elevated RASGRP4 and TIMM10B expression with reduced TNFRSF13C expression correlated with poor survival and accelerated disease progression, underscoring their prognostic significance. Our study revealed RASGRP4, TIMM10B, and TNFRSF13C as promising therapeutic targets in TNBC. Targeting these TAN-associated genes may disrupt pro-tumor immune responses, suggesting novel strategies to improve patient outcomes.